Efficacy of dietary protein against monocrotophos toxicity on some carbohydrate metabolic enzymes in rats - SHARMA, NEETA RAJ; KUSHWAH, AMEETA; KUSHWAH, H S (The Indian Journal of Animal Sciences, 2013)
A study on carbohydrate metabolic hepatic enzymes was conducted to establish the beneficial effect of dietary protein in alleviating the toxic stress ofa single or repeated intubation of monocrotophos (2 mg/kg body weight) in rats maintained on formulated isoenergetic diets under normal, protein deficient and protein supplemented dietary conditions at 20 and 5% protein levels. Acute and chronic administration of organophosphate at varying intervals induced variable responses. An accelerated rate of anaerobic glycolysis with a concomitant decreased rate of gluconeogenesis was indicated in malnourished rats after acute dosage. Chronic monocrotophos poisoning induced increased energy demand in normal rats. In protein deficient rats, the rate of glycogenolysis and glycolysis elevated to meet the primary stress response; the activity of gluconeogenic enzymes also got stimulated. However, the animals were able to counteract the toxicity of pesticide on hepatic enzymes, when fed on high protein diet.